Analysis of the Influence of Leadership Style and Motivation on Auditor Performance at the Ministry of Defense Inspectorate - Samadara, Thontje Erwin P. (Dinasti International Journal of Digital Business Management, 2025)
In an effort to achieve the organizational goals of the Inspectorate General of the Ministry of Defense of the Republic of Indonesia through effective and efficient supervision activities, an integral process is needed in the actions and activities carried out continuously by the leadership and all employees to provide adequate confidence. For this reason, high performance of the Auditor is required in completing tasks related to supervision, among others, audit, review, evaluation, monitoring, and other supervisory activities on the implementation of organizational duties and functions that are the responsibility of the Inspector General which is influenced by the work motivation of each Auditor. On the other hand, the work motivation of an Auditor can be influenced by the leadership style of a leader. This study aims to determine the influence of leadership style on the performance of Auditors through work motivation in the Inspector General of the Ministry of Defense. The type of research used is quantitative research, with a survey method. This study uses a sampling technique. In data analysis, the researcher used the Partial Least Square statistical application. The results of the study show that the participatory leadership style has a significant influence on the performance of the Auditor through the work motivation that exists in the Auditor.